2011
DOI: 10.3171/2010.9.spine1043
|View full text |Cite
|
Sign up to set email alerts
|

A computed tomography–based morphometric study of thoracic pedicle anatomy in a random United States trauma population

Abstract: Preoperative CT evaluation is important in choosing PS length, diameter, trajectory, and entry point due to variation based on spinal level, patient sex, and side of placement. These data are valuable for resident and fellow training to guide the safe use of thoracic PSs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…With the increasing number of surgical and anaesthetic procedures being done in the thoracic vertebral column all over the world, a thorough knowledge of anatomical and radiological parameters is required. 5,24,[32][33][34][35] Advent of new assistive devices like c-arm, CT scan and navigation has made these procedures a bit easy; still knowledge of pre-procedure normative data is required to decrease complication rate. The present study presents the detailed CT morphometric data of the thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the increasing number of surgical and anaesthetic procedures being done in the thoracic vertebral column all over the world, a thorough knowledge of anatomical and radiological parameters is required. 5,24,[32][33][34][35] Advent of new assistive devices like c-arm, CT scan and navigation has made these procedures a bit easy; still knowledge of pre-procedure normative data is required to decrease complication rate. The present study presents the detailed CT morphometric data of the thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
“…Minimal clinically relevant PS has 4.0 mm-diameter with 1.0 mm clearance. 33 Prior biomechanical analysis has shown that pedicle deformation and loss of purchase can occur when screw diameter is >80% of the outer cortical diameters. 34 Based on the analysis of the present study in the mid-thoracic region 76% pedicles at T4 and 62% at T5 would not accommodate a 4.0 mm PS compared to the junctional areas [T1 (2%), T11 (7%) and T12 (8%)].…”
Section: Transverse Pedicle Widthmentioning
confidence: 99%
See 1 more Smart Citation
“…However, laminectomy and placement of pedicle screws in the thoracic spine also carries risk of injury to the corresponding nerve roots, which could result in pain as well as sensory and motor deficits. Because of the smaller and more anatomically variable pedicles (Kretzer et al, 2011), misplacement of thoracic pedicle screws can occur frequently even in the hands of an experienced surgeon (Samdani et al, 2010a;Smorgick et al, 2005). The research to date has focused primarily on tEMG to ensure safe pedicle screw placement, with little reported regarding the utility of sEMG to detect pedicle breach.…”
Section: Thoracic Spinementioning
confidence: 99%
“…On searching Google scholar, Pub med and Cochrane data base we found studies describing anatomical angular direction of pedicle by imaging studies or on cadaveric bones. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] There were articles that used computer-assisted image-guided navigation (IGN) for inserting the pedicle screw using 2Dimensional (2D), Background: Pedicle screw fixation in high grade lumbar listhetic vertebral body has been nightmare for Orthopaedic and spine surgeons. This is because of abnormally positioned listhetic pedicles and nonvisualization of pedicle in conventional image intensifier (C-Arm).…”
Section: Introductionmentioning
confidence: 99%